Annual report on exchange arrangements and exchange restrictions - International Monetary Fund; International Monetary Fund- imf (Washington: International Monetary Fund, 2003)
The annual report on exchange arrangements and exchange restrictions draws on information available to the IMF from a number of sources, including that provided in the course of official staff visits to member countries, and has been prepared in close consultation with national authorities. The information is presented in a tabular format.
usc 13/06/17
Ref.
Keywords: Annual report; Exchange arrangements - annual report; Exchange restrictions -annual report